Monocytes expand with immune dysregulation and is associated with insulin resistance in older individuals with chronic HIV. - Cecilia M Shikuma; Dominic C Chow; Louie Mar A Gangcuangco; Guangxiang Zhang; Sheila M Keating; Philip J Norris; Todd B Seto; Nisha Parikh; Kalpana J Kallianpur; Beau K Nakamoto; Lorna S Nagamine; Lishomwa C Ndhlovu; et al. (PLoS ONE)
Background Rates of insulin resistance are increased in HIV-infected patients on stable antiretroviral therapy (ART). Such increase may partially be due to HIV-induced immune dysregulation involving monocytes (MO) and its subsets. Materials and methods Cross-sectional analysis of 141 HIV-infected subjects age ≥ 40 years on stable ART. Homeostatic model assessment-insulin resistance (HOMA-IR) and rates of metabolic syndrome were calculated. Subjects were classified by fasting glucose and oral glucose tolerance test (OGTT) into clinical diabetes categories. Multi-parametric flow cytometry was used to determine MO subset percentages: [classical (CD14(++)CD16(-)), intermediate (CD14(++)CD16(+)), non-classical (CD14(low/+)CD16(++)), and a recently identified fourth (CD14(low/+)CD16(-)) 'transitional' MO subset] and percentage of activated (CD38(+)HLA-DR(+)) CD8 T cells. Absolute levels of cells were calculated using clinical CBC and T cell subset data. Multiple plasma soluble biomarkers were assessed by Luminex technology. Results Median age 50 years, CD4 count (percent) 505 cells/µL (29%), and 89% male. Total MO (r=-0.23, p=0.006) and classical and non-classical MO subsets correlated negatively with CD4 percent. No correlations were seen with CD4 count as absolute values. Log-total MO and log-classical MO predicted HOMA-IR independently of HIV immuno-virologic and diabetes risk factors (β=0.42, p=0.02 and β=0.35, p=0.02, respectively) and were increased in subjects with metabolic syndrome (p=0.03 and p=0.05 respectively). Total and/or subset MO levels correlated with multiple soluble plasma biomarkers including CRP, IL-6, MMP-9, MPO, SAA, SAP and tPAI-1, with tPAI-1 independently predicting HOMA-IR (β=0.74, p<0.001). Conclusions MO levels increase with worsening HIV immune dysregulation as assessed by CD4 percent. CD4 percent may provide additional information about MO and metabolic risk in this population beyond absolute values. MO, and specifically classical MO, may contribute to insulin resistance and metabolic syndrome during chronic HIV infection. Multiple soluble plasma biomarkers including tPAI-1 increase with increase in MO. Levels of tPAI-1 independently predict the development of insulin resistance.